2009
DOI: 10.1176/appi.neuropsych.21.3.328
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Revealing Impaired P50 Gating in Antisocial Personality Disorder

Abstract: The authors investigated preattentive filtering assessed by P50 gating in nine participants with antisocial personality disorder (ASPD) and seven with adult-onset antisocial behavior (AAB). Relative to 15 comparison subjects, gating was impaired in ASPD, suggesting abnormal pre-attentive filtering in pathological impulsivity.Repetition-induced reduction in P50 amplitude (P50 gating) could reflect a preattentive mechanism that filters out irrelevant information, affecting cognitive and motor processes and task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…Preliminary results showed later P50 peak latencies and reduced P50 ASG in subjects with ASPD, but not in subjects with adult-onset antisocial behavior, compared to controls (Lijffijt et al, 2009). There was also a trend for a more pronounced P50 ASG impairment in subjects endorsing more conduct disorder symptoms, similar to relationships between ASPD symptoms and changes in evoked potentials reflecting higher-order mechanisms (Bauer, 2001; Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Preliminary results showed later P50 peak latencies and reduced P50 ASG in subjects with ASPD, but not in subjects with adult-onset antisocial behavior, compared to controls (Lijffijt et al, 2009). There was also a trend for a more pronounced P50 ASG impairment in subjects endorsing more conduct disorder symptoms, similar to relationships between ASPD symptoms and changes in evoked potentials reflecting higher-order mechanisms (Bauer, 2001; Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 86%
“…Analyses were limited to males because only 4 women with ASPD completed electrophysiological testing. Groups in this paper differed from our previous paper (Lijffijt et al, 2009): to increase sample size and generalizability controls were now allowed to have first-degree relatives with a psychiatric disorder (26 ASPD, 11 controls; no report: 4 ASPD, 6 controls), and to endorse ASPD symptoms without meeting full childhood or adulthood criteria. Six subjects with ASPD and 7 controls were in both studies.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed P50 gating impairments in subjects with Alzheimer dementia (Thomas et al, in press), childhood-onset antisocial personality disorder (Lijffijt, Moeller, Boutros, Burroughs, et al, in press), posttraumatic stress disorder (Karl, Malta, & Maercker, 2006), panic disorder (Ghisolfi et al, 2006), schizotypal personality disorder (Cadenhead, Light, Geyer, & Braff, 2000; Wan, Crawford, & Boutros, 2007; Wang, Miyazato, Hokama, Hiramatsu, & Kondo, 2004), cocaine abuse (Boutros, Gooding, Sundaresan, Burroughs, & Johanson, 2006; Fein, Biggins, & MacKay, 1996), schizophrenia (Bramon, Rabe-Hesketh, Sham, Murray, & Frangou, 2004; Brockhaus-Dumke, Schultze-Lutter et al, 2008; De Wilde, Bour, Dingemans, Koelman, & Linszen, 2007; Patterson et al, 2008), and bipolar I disorder (Lijffijt, Moeller, Boutros, Steinberg, et al, in press; Olincy& Martin, 2005; Schulze et al, 2007), suggesting a common underlying filter deficit across a wide range of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Given the comorbidity of antisocial personality disorder (ASPD) and substance use disorders (SUDs) reported to characterize antisocial individuals with schizophrenia (Hodgins, 2004; Moran and Hodgins, 2004; Mueser et al, 1997), and the effects these conditions separately may have upon EEG functioning (Costa and Bauer, 1997; Lijffijt et al, 2009; Lindberg et al, 2005), it was important in the present study to assess for comorbidities with these illnesses. Overall rates for antisocial personality and substance use disorders in this sample, however, were very low.…”
Section: Methodsmentioning
confidence: 99%